2022
DOI: 10.3390/plants11233289
|View full text |Cite
|
Sign up to set email alerts
|

PGP-Bacterium Pseudomonas protegens Improves Bread Wheat Growth and Mitigates Herbicide and Drought Stress

Abstract: The reaction of plants to simultaneous stress action and treatment with biological stimulants still remains poorly studied. Laboratory and field experiments have been conducted to study the growth and yield of bread wheat (Triticum aestivum L.) of the variety Ekada 113; stress markers and quantitative ratios of phytohormones in plants under insufficient soil moisture; the effects of spraying with herbicide containing 2,4-D and dicamba and growth-stimulating bacterium Pseudomonas protegens DA1.2; and combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…For canola, against the background of metsulfuron-methyl, this effect was shown for the first time. However, it was previously observed when combining other crops with herbicides of a different chemical nature [ 16 , 17 , 18 , 19 , 20 ]. The study of Ibrahim et al [ 38 ] concluded that foliar spray of pongamia oil alleviated the toxic effects of glyphosate on tomato plants in the form of increased root and shoot biomass while reducing MDA and O2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For canola, against the background of metsulfuron-methyl, this effect was shown for the first time. However, it was previously observed when combining other crops with herbicides of a different chemical nature [ 16 , 17 , 18 , 19 , 20 ]. The study of Ibrahim et al [ 38 ] concluded that foliar spray of pongamia oil alleviated the toxic effects of glyphosate on tomato plants in the form of increased root and shoot biomass while reducing MDA and O2.…”
Section: Discussionmentioning
confidence: 99%
“…Motamedi et al [ 17 ] described a positive effect of the native plant growth-promoting bacteria on plant biomass in the presence and absence of imazethapyr herbicide. The protective effect of strains of Pseudomonas putida [ 18 ], P. protegens DA1.2 [ 19 ], P. chlororaphis PAS18 [ 20 ], and Azotobacter salinestris KF470807 [ 21 ] was studied. In the described experiments, an improvement in the growth of agricultural plants and the reduction of herbicide stress manifestations after spraying with bacterial cultures were recorded.…”
Section: Introductionmentioning
confidence: 99%
“…The interactions between the microorganisms of plant rhizospheres are complex and may be negative [ 7 , 11 , 12 ], neutral, or beneficial on the basis of their effects on plant growth [ 13 ]. It is necessary to investigate all aspects of the life of plant growth-promoting (PGP) microorganisms, which provide benefits for plants due to the consortium effect and alleviate drought stress in crop plants [ 13 , 14 ], thereby improving growth and productivity [ 9 , 15 , 16 , 17 , 18 , 19 , 20 ]. Some bacterial isolates simultaneously are able not only to increase the growth of agricultural plants such as wheat, but are also able to decrease the growth of grass weed [ 7 , 21 ] and fungal diseases of wheat [ 7 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pseudomonas fluorescens BRG100 produces substances with herbicidal activity on weed pest and could be used as bioherbicide [ 23 ]. The mechanisms of beneficial action of PGP bacteria and fungi for plant organisms involve releasing a wide range of important secondary metabolites: phytohormones [ 10 , 19 , 23 , 24 , 25 , 26 ] and organic and amino acids [ 12 , 24 , 25 ]. PGP bacteria could also enhance: photosynthesis [ 17 , 27 , 28 , 29 ], the nutrient uptake by solubilizing inorganic elements [ 7 , 25 , 28 , 29 , 30 ]; the biosynthesis of siderophores [ 10 , 13 , 16 , 20 , 25 ]; antioxidant defense systems [ 7 , 13 , 25 , 28 , 29 ]; and stress-responsive genes expression [ 13 , 15 , 16 , 19 , 26 , 31 , 32 ] under the influence of stress factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation